Nidogen in development and disease - Töpfer, Uwe; Holz, Anne (Frontiers in Cell and Developmental Biology, 2024)
Nidogen, also known as entactin, is a multifunctional glycoprotein that plays a crucial role in the maintenance of the basement membrane (BM), morphogenesis and neuronal plasticity. This review aims to provide an overview of the structural features, molecular interactions and diverse functions associated with Nidogen. As a bridging molecule within the BM, Nidogen acts as a linchpin connecting various extracellular matrix (ECM) components. Its involvement in tissue development, homeostasis, and pathological conditions underscores its biological and medical significance. We discuss the current state of knowledge regarding Nidogen’s role in tissue maintenance, cell adhesion, migration, and signaling, shedding light on its intricate contributions to physiological and pathological processes.